Train drivers mental workload and alertness under simulated conditions based on electroencephalogram signals / Nurul Izzah Abd Rahman - Nurul Izzah, Abd Rahman (2013)
Train driving may seem simple. Drivers are able to handle train journeys after going through trainings. However, accidents do happen and most of these accidents can be related to human failure. Adverse driving conditions are factors that lead to increased risk of train drivers‟ failure in performing their task. Thus, there is a need for assessing human factors due to the exposure of different driving conditions. There are two main objectives in this study. The first is to investigate empirically Malaysian train drivers‟ mental workload and alertness in various conditions. The second objective is to determine the significant pattern of various mental workloads and alertness of train drivers with reference to different conditions. The data were collected through experimental study. Fifteen professional train drivers were involved in the study. The experiments were performed in three types of conditions; during daytime, rainy and rainy night. Participants were required to use the train driving simulator set for a total duration of sixty minutes. Electroencephalogram (EEG) signal were collected from six significant placements (FZ, PZ, O1, O2, P3 and P4) to determine the mental workload and alertness required for each task. The mean alpha power was monitored as this signal reflects the variation in mental workload level. Night and rainy setting has shown significant difference pattern from other conditions. The result highlighted that 37% of difference between normal daytime driving and rainy night driving even at the early driving duration. It can be understood that during this driving situation, the mental workload tends to be high and sleepiness occurs which is a sign of low vigilance. This finding also shows that the train drivers tend to have a decrease in mental workload after six minutes of driving during rainy night shift. On the other hand, beta amplitude presented that during rainy and night drive, increment was recorded which may be occurred because of difficulty to see through in the dark. In the conclusion, the study has shown a significant pattern for night raining condition. It is also highlighted that during night and rainy, the mental workload increases 37% from sunny condition. Meanwhile, it was found out that after six minutes of rainy night driving, a lower mental workload appeared among the train drivers which showing detachment on the works. In addition, it was found out that there is difficulty in term of vision among the train drivers during rainy night drive. It is significant to be aware on this condition since it is very dangerous. This result highlighted that an ergonomic work schedule and work design is needed to tackle the problem to avoid human error.